2020
DOI: 10.1111/apha.13519
|View full text |Cite
|
Sign up to set email alerts
|

Activated FMS‐like tyrosine kinase 3 ameliorates angiotensin II‐induced cardiac remodelling

Abstract: Aim FMS‐like receptor tyrosine kinase 3 (Flt3) has been reported to be increased in cardiomyocytes responding to ischaemic stress. This study was to determine whether Flt3 activation could ameliorate pressure overload‐induced heart hypertrophy and fibrosis, and to elucidate the mechanisms of action. Methods In vivo cardiac hypertrophy and remodelling experiments were conducted by infusing angiotensin II (Ang II) chronically in male C57BL/6 mice. Flt3‐specific ligand (FL) was administered intraperitoneally ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…In line with these findings, BEN has previously been shown to modulate cytokine secretion in B-cells via the p38 MAP kinase pathway [ 112 ], which is activated downstream of Flt3 [ 119 ]. Further, Flt3 activation can suppress autophagy [ 120 ], which promotes long-term cross-presentation in murine DCs [ 121 ], and increase DC lifespan [ 122 ]. This is suggestive of a potential mechanism by which BEN induces increased expression of Flt3 and pathways by which enhanced Flt3 activation may alter DC phenotype and function in the context of alloreactivity.…”
Section: Immunomodulatory Effects Of Benmentioning
confidence: 99%
“…In line with these findings, BEN has previously been shown to modulate cytokine secretion in B-cells via the p38 MAP kinase pathway [ 112 ], which is activated downstream of Flt3 [ 119 ]. Further, Flt3 activation can suppress autophagy [ 120 ], which promotes long-term cross-presentation in murine DCs [ 121 ], and increase DC lifespan [ 122 ]. This is suggestive of a potential mechanism by which BEN induces increased expression of Flt3 and pathways by which enhanced Flt3 activation may alter DC phenotype and function in the context of alloreactivity.…”
Section: Immunomodulatory Effects Of Benmentioning
confidence: 99%
“…However, one report found that BEN inhibits canonical STAT3 signaling ( 32 ). STAT3 is one of several known signaling molecules downstream of Flt3 providing essential signals for differentiation, survival, and proliferation ( 13 , 48 51 ). We hypothesized that, by inhibiting STAT3, BEN interrupts Flt3-STAT3 signaling causing a compensatory upregulation of Flt3 surface expression.…”
Section: Resultsmentioning
confidence: 99%
“…In-depth knowledge of developmental mechanisms of gene regulation does not only add to our abilities to care for pregnant women and aid a healthy start into human life. Reactivation of developmental gene expression patterns may also help us to better understand, for example, remodelling processes later in life, 18,19 or recognize embryonic or foetal mechanisms of, for example, fibrosis in the adult organism, with hopeful therapeutic perspectives 20,21 Other recent results with implications for perinatal healthcare include results on thyroid hormone dysregulation, which impairs both neuronal and glial cell development. 22 Also, during early human development, the mammalian circadian system develops gradually.…”
Section: Pregnancymentioning
confidence: 99%
“…In‐depth knowledge of developmental mechanisms of gene regulation does not only add to our abilities to care for pregnant women and aid a healthy start into human life. Reactivation of developmental gene expression patterns may also help us to better understand, for example, remodelling processes later in life, 18,19 or recognize embryonic or foetal mechanisms of, for example, fibrosis in the adult organism, with hopeful therapeutic perspectives 20,21 …”
mentioning
confidence: 99%